Szanse kreowania tożsamości i wizerunku obszaru turystycznego poprzez zrównoważony rozwój turystyki - Nawrocka, Elżbieta (Opportunities for creating identity and image of a tourist area by developing sustainable tourism based on an example of Jelenia Góra district communes, 2005)
The article presents issues related to creating local identity and image of a tourist area, which result in the need for bringing into effect the concept of sustainable social and economic development, including tourism. Local government plays significant role in this process, because it influences its success to the greatest extend. The hereby article presents research results conducted by means of a direct method - a questionnaire carried out among individuals dealing in local tourism development and representing particular communal offices of Jelenia Góra district.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 118-129